Subjective social status in collective sports (Research, Society and Development, 2022)
Subjective social status is the perception of an individual about his social position in the most diverse contexts of life. The aim of this study was to compare the subjective social status among collective sport athletes. A total of 115 male athletes participated in this study: soccer, volleyball, handball and basketball. The assessment of the perception of subjective social status was performed using the MacArthur scale. For data analysis the chi-square, Anova one way and Kolmogorov Smirnov tests were used. According to the data, it can be observed that the soccer athletes presented the lowest scores of current subjective social status in the club (X: 4.9; ± 2.0) and in the family context (X: 7.0; ± 2.0). In addition, soccer athletes have a higher prevalence of dissatisfaction (87.2%; n = 42). It was concluded that soccer athletes have a higher perception of dissatisfaction with subjective social status.